Sedimentation rates of nutrients and particulate material in pond mariculture of shrimp (Litopenaeus vannamei) carried out with different management strategies - Junior, Ambrosio Paula Bessa; Flickinger, Dallas Lee [UNESP]; Henry-Silva, Gustavo Gonzaga (Elsevier, 2021)
Marine shrimp farming is an important economic activity in tropical and subtropical regions, but its expansion has contributed to the increase of nutrients and organic matter in coastal ecosystems. Thus, this work evaluated the sedimentation rates of nutrients and particulate matter in marine shrimp (Litopenaeus vannamei) grow-out in earthen ponds. Three different stocking densities of the shrimp were evaluated over a period of approximately 79 days: M1: 92 shrimps.m−2; M2: 14 shrimps.m−2 and M3: 8 shrimps.m−2. Transparency, temperature, pH and dissolved oxygen remained within the ideal ranges for L. vannamei pond mariculture, whereas the salinity was outside the recommended range. With the exception of total inorganic and organic carbon, the sedimentation rates of nutrients were significantly higher in M3 for the first sample period. This was perhaps due to the management of the first phase (greenhouse) requiring high inputs for a high initial population and the consequent accumulation of suspended solids and organic matter. The M1 showed decreases throughout the experimental period for the sedimentation rates of nutrients, which may have been subjected to bacterial decomposition. Decreasing sedimentation rates in the M2 were only observed for ammonia, nitrate and total-N. This trend may be associated with the primary production in the earthen pond system as suggested by the increasing of chlorophyll-α throughout the cultivation. In conclusion, the sedimentation rates of nutrients in marine shrimp aquaculture are influenced by a high stocking density and the quantity of feed offered per unit of production area.
Keywords: Earthen ponds; Greenhouse; Nutrients; Sedimentation rate; Shrimp